She wore a yellow ribbon [videorecording (DVD)] - Ford, John, 1894-1973; Wayne, John, 1907-1979; Dru, Joanne, 1923-1996; Agar, John, 1921-2002; Johnson, Ben, 1918-1996 (John Wayne collection., 2007)
A desperately short-staffed cavalry outpost must try to stop an Indian invasion.